The role of lipid profile and inflammotry markers in diffrentiating between focal and generalized types of seizures in pediatric epilepsy patients - Bilge, Serap; Bilgin, Hüseyin (The European Research Journal, 2025)
Objectives: Seizures result from excessive and abnormal neuronal excitation, accompanied by pathophysiological processes such as inflammation, oxidative stress, and apoptotic cell death. Previous studies have demonstrated that patients with epilepsy often exhibit dysregulated inflammatory, vascular, and metabolic pathways, with certain seizure types associated with high pro-inflammatory cytokines. We aimed to investigate whether lipid profile parameters and inflammatory markers can be used to differentiate between focal and generalized seizures in pediatric epilepsy patients. Methods: A total of 100 pediatric epilepsy patients and 100 age- and sex-matched healthy controls were recruited at Diyarbakır Children's Hospital between December 2021 and March 2023. Ethical approval was obtained from the institutional review board, and informed consent was secured from parents/guardians. Lipid levels (triglycerides, total cholesterol, low-density lipoprotein [LDL] cholesterol, high-density lipoprotein [HDL]) cholesterol) and inflammatory markers (ferritin, glucose, white blood cell count [WBC], C-reactive protein [CRP]) were analyzed using standard laboratory methods. Results: The mean age was 9.2±4.4 years in the epilepsy group and 8.9±4.9 years in controls. Triglycerides, LDL, and total cholesterol levels were significantly higher in epilepsy patients compared to controls (P